The cult of Henry VI: sainthood, kingship and memory - Lloyd Williams, Frederick A. S. (2024)
Defeated by the French, mentally debilitated and twice deposed, in 1471 Henry VI, king of England, met a gruesome end and was murdered in the Tower of London. Bringing the Lancastrian dynasty to a close, Henry is often considered to be one of the worst monarchs to have ever ruled the country. Yet, swiftly following his death, Henry gained widespread fame as a holy figure so powerful that he reportedly worked numerous miracles ranging from finding lost objects to bringing people back from the dead. Pilgrims travelled en masse to Henry’s burial places, devotees sung songs in his honour and artists across the country rendered the king’s image on church rood screens and walls.